A 17.5dB wide-dynamic range high-efficiency RF-to-DC power converter for wireless energy harvesting. Issue 3 (3rd July 2022) - Alhoshany, Abdulaziz
ABSTRACT: A novel reconfigurable RF-to-DC power converter is proposed for wireless energy harvesting. The proposed RF rectifier employs low-threshold transistors with cross-coupled configuration to enhance the flow of the forward current to the load at low input RF power and adaptive stacking diodes to reduce the leakage current by lowering the driving voltage of the rectifying PMOS transistors at high input RF power. The proposed rectifier utilises the body biasing technique to modulate the threshold voltage and minimises the leakage current of the feedback diodes. The proposed novel techniques improve efficiency and extend the dynamic range. The prototype is implemented in a 65 nm CMOS technology and occupies an active area of 0.0148 mm 2 . The proposed rectifier achieves a peak power conversion efficiency (PCE) of 76% with a load of a 100-KΩ load at the industrial, scientific, and medical band 433 MHz, and the achieved sensitivity of the rectifier is −18.5 dBm for 1 V DC output voltage. The proposed rectifier offers PCE at −35 dBm of 45.6%, which is the best low-power performance. Compared to the state-of-the-art rectifiers, the proposed design achieves an excellent wide-dynamic range of 17.5 dB, which is ten times better than the conventional cross-coupled rectifier.